The Individual Features Of Indonesian-Chinese Mini-Novels - Feng, Ma (Lingua Cultura, 2011)
This article talks about mini-novels in the new period of Indonesian Chinese Literature.Â Through the overall developing trend of mini-novelsâ€™ corpuses, analyzes the individual creativeÂ features: firstly, the humor of Mo Mingmiaoâ€™s Mini-novels; secondly, the compassion of Xiao Xingâ€™sÂ Mini-novels; thirdly, Yuan Niâ€™s emotional sonata of The Lost Key-ring. By combination of themes andÂ techniques of the three mini-novels corpuses, the article focuses on the analysis of three writersâ€™Â distinctive writing style.